The Utilization of Self-Access Centre (SAC) for Independent Learning of German Language Education Students - Ayu, Aniza Kartika; Sobara, Iwa (Nexus Publishing NXP, 2025)
Self-Access Centre (SAC) is one of the learning facilities that supports students in developing their language skills independently. In the context of German language education, SAC provides various resources and support that can help students manage their own learning outside of the classroom. However, how students actually use SAC, what influences their decision to use it, and how they perceive its effectiveness may vary. This study explores how German language education students at Universitas Negeri Malang utilize the SAC for independent learning. It also investigates the factors that influence their usage and their perceptions of SAC’s role in improving their German skills. Data were collected through a semi-open questionnaire completed by 49 students and in depth interviews with a separate group of seven students. This study focuses on three key aspects: students’ frequency of visits, their use of available facilities and tutor assistance, and their motivation for using the SAC. The results show that students are encouraged to use the SAC not only because of its comprehensive resources and support from tutors, but also through peer influence. Most students agree that the SAC provides a helpful environment that boosts their motivation and interest in learning German independently. These findings suggest that the SAC can play a significant role in supporting autonomous language learning when its resources align with student needs and preferences.